2015
DOI: 10.1021/jf502229f
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate Flocs and the Clarification of Sugar Cane Juice from Whole of Crop Harvesting

Abstract: Sugar cane biomass is one of the most viable feedstocks for the production of renewable fuels and chemicals. Therefore, processing the whole of crop (WC) (i.e., stalk and trash, instead of stalk only) will increase the amount of available biomass for this purpose. However, effective clarification of juice expressed from WC for raw sugar manufacture is a major challenge because of the amounts and types of non-sucrose impurities (e.g., polysaccharides, inorganics, proteins, etc.) present. Calcium phosphate flocs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The wide band observed at 3355 cm −1 is related to hydrogen bonding and hydroxyl (‐OH) stretching vibrations. The band at 2930 cm −1 arises from the C–H stretching vibration of the methyl group, which may be related to the presence of polysaccharides (Thai et al ., 2015). The band near 2930 cm −1 arises from the stretching vibration of the sp 3 C–H group in the alkyl chains of polysaccharides and proteins (Thai et al ., 2015; Shi et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The wide band observed at 3355 cm −1 is related to hydrogen bonding and hydroxyl (‐OH) stretching vibrations. The band at 2930 cm −1 arises from the C–H stretching vibration of the methyl group, which may be related to the presence of polysaccharides (Thai et al ., 2015). The band near 2930 cm −1 arises from the stretching vibration of the sp 3 C–H group in the alkyl chains of polysaccharides and proteins (Thai et al ., 2015; Shi et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It may vary from increasing tonnage capacity to diversifying in related or unrelated product lines, for example, Integrated sugar complex is a diversified and valueadded phenomenon producing green energy-bio-ethanol (reduces Co 2 and Co 4 ), bio-power and bio-manure (Solomon, 2011;Ramaswamy et al, 2006). Whole sugarcane biomass (food cum bio-commodities) is usable that symbolizes that all leftovers across whole value chain can yield significant revenues (Thai et al, 2015). Campos-Ortiz and Oviedo-Pacheco ( 2014) found that mills having power generation plants are earning huge revenues and profits as compared to those who haven't adopted ISC model yet.…”
Section: Operations' Diversification and Growthmentioning
confidence: 99%
“…The changes in floc structure, along with the increasing Na + concentration, could be associated with the dispersive properties of Na + ions. The general increase in size may be due to electrostatic repulsion between calcium phosphate particles and/or electrostatic repulsion between the microflocs because of the dispersive action of Na + ions (Thai, Moghaddam and Doherty 2015).…”
Section: Sodiummentioning
confidence: 99%